2010
DOI: 10.1177/0093650209356438
|View full text |Cite
|
Sign up to set email alerts
|

Does God Matter? Religious Content and the Evaluation of Comforting Messages in the Context of Bereavement

Abstract: Many people use religious belief and practice as a resource for coping with distress. However, the influence of religious content in comforting messages has yet to be examined. The current study was designed to examine how comforting messages that vary in person centeredness and incorporate different kinds of religious content are evaluated by people who vary in intrinsic religiosity and styles of religious coping. College students ( N = 312) were asked to imagine that a grandparent had died and to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Because of the strong correlations among the third-party observers' variables, we averaged these scores to create a composite variable for use in the analyses. Prior research combines items such as sensitivity and supportiveness to measure support quality (Jones & Burleson, 2003;Wilkum & MacGeorge, 2010); therefore, we adopt the label support quality for this variable (M = 4.18, SD = 1.50). We next evaluated whether the support receivers who completed the follow-up survey differed significantly from those who did not.…”
Section: Preliminary Analysesmentioning
confidence: 99%
“…Because of the strong correlations among the third-party observers' variables, we averaged these scores to create a composite variable for use in the analyses. Prior research combines items such as sensitivity and supportiveness to measure support quality (Jones & Burleson, 2003;Wilkum & MacGeorge, 2010); therefore, we adopt the label support quality for this variable (M = 4.18, SD = 1.50). We next evaluated whether the support receivers who completed the follow-up survey differed significantly from those who did not.…”
Section: Preliminary Analysesmentioning
confidence: 99%
“…Although person centeredness is a well-established means of operationalizing message quality in comforting messages (Burleson, 2003), it does not attend to all of the verbal and nonverbal characteristics that can contribute to the perceived quality of comforting interactions (e.g., nonverbal immediacy, religious content; Jones & Guerrero, 2001;Wilkum & MacGeorge, 2010).…”
Section: Communication Reports 71mentioning
confidence: 99%
“…Verbal person-centered (VPC) messages represent a hierarchical typology of emotional support that vary in their recognition, elaboration, and legitimization of the feelings of others (Burleson, 1985). Messages high in VPC are consistently perceived by support recipients as the most sensitive and effective at alleviating emotional distress as compared to low VPC messages (Burleson & Samter, 1985;High & Dillard, 2012;Jones, 2004;Jones & Guerrero, 2001;Rack, Burleson, Bodie, Holmstrom, & Servaty-Seib, 2008;Wilkum & MacGeorge, 2010). Since this investigation is focused on the factors that help an individual achieve emotional relief, messages that vary in level of VPC act as one potential outlet for promoting this specific social support outcome.…”
Section: Third I Want To Express My Sincerest Gratitude To My Parentmentioning
confidence: 99%
“…Results indicated that grief messages high in VPC were perceived by participants as the most helpful. Wilkum and MacGeorge (2010) also examined VPC messages in the context of bereavement. The purpose of their study was to explore the relationship between religious content and perceptions of comforting messages.…”
Section: Types Of Social Supportmentioning
confidence: 99%
See 1 more Smart Citation